A broad phylogenetic survey unveils the diversity and evolution of telomeres in eukaryotes - Fulnecková, Jana; Sevcíková, Tereza; Fajkus, Jirí; Lukesová, Alena; Lukes, Martin; Vlcek, Cestmír; Lang, B Franz; Kim, Eunsoo; Eliás, Marek; Sykorová, Eva (Genome biology and evolution, 2013)
Telomeres, ubiquitous and essential structures of eukaryotic chromosomes, are known to come in a variety of forms, but knowledge about their actual diversity and evolution across the whole phylogenetic breadth of the eukaryotic life remains fragmentary. To fill this gap, we employed a complex experimental approach to probe telomeric minisatellites in various phylogenetically diverse groups of algae. Our most remarkable results include the following findings: 1) algae of the streptophyte class Klebsormidiophyceae possess the Chlamydomonas-type telomeric repeat (TTTTAGGG) or, in at least one species, a novel TTTTAGG repeat, indicating an evolutionary transition from the Arabidopsis-type repeat (TTTAGGG) ancestral for Chloroplastida; 2) the Arabidopsis-type repeat is also present in telomeres of Xanthophyceae, in contrast to the presence of the human-type repeat (TTAGGG) in other ochrophytes studied, and of the photosynthetic alveolate Chromera velia, consistent with its phylogenetic position close to apicomplexans and dinoflagellates; 3) glaucophytes and haptophytes exhibit the human-type repeat in their telomeres; and 4) ulvophytes and rhodophytes have unusual telomere structures recalcitrant to standard analysis. To obtain additional details on the distribution of different telomere types in eukaryotes, we performed in silico analyses of genomic data from major eukaryotic lineages, utilizing also genome assemblies from our on-going genome projects for representatives of three hitherto unsampled lineages (jakobids, malawimonads, and goniomonads). These analyses confirm the human-type repeat as the most common and possibly ancestral in eukaryotes, but alternative motifs replaced it along the phylogeny of diverse eukaryotic lineages, some of them several times independently.
Keywords: Base Sequence; Telomere; Genetic Variation; Eukaryota; telomery; molekulární evoluce; Humans; fylogeneze; lidé; sekvence nukleotidů; Molecular Sequence Data; Genome; tandemové repetitivní sekvence; DNA řas; genetická variace; genom; Phylogeny; molekulární sekvence - údaje; DNA, Algal; Evolution, Molecular; Tandem Repeat Sequences